Pemberdayaan Demokrasi Masyarakat Dalam Meningkatkan Lingkungan Baik Dan Sehat - Juliaster Marbun; Samuel Brahmana; Agustinus Laia; Enjeli Ratna Sari Nduru; Sri Wahyuni Manurung (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this PkM activity is to form the character of a community that cares about democracy and has a Pancasila profile background that has understanding, active involvement and collective responsibility in maintaining and improving the quality of the environment, with the ultimate goal of creating a good and healthy environment for all. This activity was carried out in Batang Kuis Pekan village, Batang Kuis District, Deli Serdang Regency, North Sumatra Province. The results of the activities are being able to adapt well so that there is a cooperative relationship between the village, students and the PkM team in Batang Kuis Pekan Village, understanding throughout the community about good democratic socialization in maintaining a healthy environment, contributing to the success of the 2024 ELECTION. Through the activities carried out, It is hoped that the community can become active agents of change in keeping the environment good and healthy, and able to play an active role in the decision-making process relating to environmental problems in their area as a form of empowering good and healthy community democracy.